Quantitative and Qualitative Investigations of Music Participation: A Multiple Study Dissertation - Kelley, James (My University, 2015)
University of Washington Abstract Quantitative and Qualitative Investigations of Music Participation: A Multiple Study Dissertation James F. Kelley Chair of the Supervisory Committee: Professor, Steven M. Demorest Introduction: The purpose of this dissertation is to contribute to the body of research that has investigated music participation within the field of music education. This dissertation contains four papers on the topic of music participation including a literature review, two quantitative studies, and one qualitative study. While the primary focus of this dissertation is the investigation of music participation, each paper also explores themes of gender and personal identity. A brief summary of each paper contained within the dissertation is described below. Paper One: The purpose of this review is to identify factors that have been associated with music participation in existing scholarship. This paper organizes findings thematically, across research methodologies and musical domains. Synthesis of research findings from extant literature suggests that personal beliefs or characteristics, social influences, and socio-cultural influences impact music participation choices. This paper also provides implications for practitioners and future music researchers Paper Two: The purpose of this study is to empirically test the influence of cultural gender norms on adolescents’ interest in music activities. Using an experimental design, middle school participants (N=246) were assigned to either a primed condition where students were asked to consider their gender identity or a control condition; all participants took a survey on interest in music activities. Findings suggest adolescents who had been primed to think about their gender identity rate music activities, including stereotypically masculine and feminine activities, significantly more positively than the control group. Paper Three: The primary author of this paper is Steven M. Demorest; the paper was co-authored by this dissertation author and Peter Q. Pfordresher. The purpose of this investigation was to explore the role of musical background and personal attitudes about music in predicting students’ decisions to participate in elective music instruction in junior high and how those same variables related to their actual singing ability. Findings suggest that family music participation and positive attitudes toward music, particularly their view of themselves as musicians, can predict with 73% accuracy which students within the sample enrolled in elective music. Musical self-concept was also a unique predictor of singing accuracy performance, suggesting a connection between students’ actual singing ability and their view of themselves as musicians. Paper Four: Although community music activities can take many forms, a “participatory ethos” is central to most community music endeavors. Karaoke is a common music activity that brings people together to experience a shared musical event. The case study used for this investigation is a karaoke culture at an LGBT establishment in the Pacific Northwest of the United States. This study focuses on the formation of community as well as identity through karaoke performance. Additionally, the application of Turino’s framework of participatory and presentational performance was used to examine how musical behaviors may encourage the formation of community and identity. Findings within this case study reveal the importance of the roles of the participants, the role of the facilitator, the agency of the individual, the fixity of musical forms, and musical texture to promote participatory experiences.
Thesis (Ph.D.)--University of Washington, 2015
Keywords: Gender; Karaoke; Musical self-concept; Music Participation; Singing Accuracy; Music education; music